Extinction of experience: the loss of human–nature interactions. Issue 2 (1st March 2016) - Soga, Masashi; Gaston, Kevin J
Abstract : Increasingly, people are becoming less likely to have direct contact with nature (natural environments and their associated wildlife) in their everyday lives. Over 20 years ago, Robert M Pyle termed this ongoing alienation the "extinction of experience", but the phenomenon has continued to receive surprisingly limited attention. Here, we present current understanding of the extinction of experience, with particular emphasis on its causes and consequences, and suggest future research directions. Our review illustrates that the loss of interaction with nature not only diminishes a wide range of benefits relating to health and well‐being, but also discourages positive emotions, attitudes, and behavior with regard to the environment, implying a cycle of disaffection toward nature. Such serious implications highlight the importance of reconnecting people with nature, as well as focusing research and public policy on addressing and improving awareness of the extinction of experience.